The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.phytochem.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

On-line detection of root-induced volatiles in Brassica nigra plants infested with Delia radicum L. root fly larvae

Abstract: Plants emit various volatile organic compounds (VOCs) upon herbivore attack. These VOC emissions often show temporal dynamics which may influence the behavior of natural enemies using these volatiles as cues. This study analyzes on-line VOC emissions by roots of Brassica nigra plants under attack by cabbage root fly larvae, Delia radicum. Root emitted VOCs were detected using Proton-Transfer-Reaction Mass Spectrometry (PTR-MS) and Gas Chromatography-Mass Spectrometry (GC-MS). These analyses showed that several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 59 publications
2
80
1
Order By: Relevance
“…3A). Enzyme assays were performed with 2-phenylethyl isothiocyanate, which is one of the main root volatiles of Brassica plants (32). The temperature optimum was found at 40°C with 4.4 U mg Ϫ1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Enzyme assays were performed with 2-phenylethyl isothiocyanate, which is one of the main root volatiles of Brassica plants (32). The temperature optimum was found at 40°C with 4.4 U mg Ϫ1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the plant species studied, volatile blends released belowground by plant roots can be characterized by compounds belonging to various chemical families, particularly terpenoids (Rasmann et al 2005;Lin et al 2007;Ali et al 2010), fatty acid derivatives (Gfeller et al 2013) or sulphur-containing compounds (Ferry et al 2007;Crespo et al 2012;Danner et al 2015). Important ecological roles have been associated with root-emitted VOCs (Fig.…”
Section: Plant Roots Release Vocs Involved In Belowground Biotic Intementioning
confidence: 99%
“…GC-MS and proton transfer reaction-mass spectrometry (PTR-MS) analyses have shown that insect-damaged Brassica roots release mainly highly volatile sulphur compounds (methanethiol, dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide) and glucosinolate breakdown products (thiocyanates and isothiocyanates) in the soil, with a VOC emission pattern depending on the plant species studied Danner et al 2012;Crespo et al 2012;Danner et al 2015). To date, PTR-MS analyses of root-emitted VOCs have been performed only on potted Brassica spp.…”
Section: Td-gc-msmentioning
confidence: 99%
See 2 more Smart Citations